Impact of Medicare Part D on mental health treatment and outcomes for dual eligible beneficiaries with HIV. Issue 4 (3rd April 2019) - Belenky, Nadya; Pence, Brian W.; Cole, Stephen R.; Dusetzina, Stacie B.; Edmonds, Andrew; Oberlander, Jonathan; Plankey, Michael; Adedimeji, Adebola; Wilson, Tracey E.; Cohen, Jennifer; Cohen, Mardge H.; Milam, Joel E.; et al.
ABSTRACT: Depression is common among women with HIV and untreated depression can result in poor quality of life and worsen HIV outcomes. Women with HIV who are dually enrolled in Medicaid and Medicare faced a potential disruption in medication access when Medicare Part D was implemented in 2006. The goal of this study was to estimate the effects of Medicare Part D implementation on antidepressant use, depressive symptoms, and hospitalization in Medicaid-Medicare dual eligible women with HIV. This study used 2003–2008 data from the Women's Interagency HIV Study. The effects of Medicare Part D were estimated using a difference-in-differences approach, adjusting for temporal trends using a matched control group of Medicaid-only enrollees. Before Medicare Part D implementation, dual eligibles differed from Medicaid-only enrollees in antidepressant use and hospitalization, despite having identical prescription drug coverage through Medicaid. For dual enrollees, the transition to Medicare Part D was not associated with changes in antidepressant use, depressive symptoms, or hospitalization. We did not find disruptive effects on antidepressant use and related outcomes among dual eligibles in this study. Stable antidepressant use may be due to better access to medical care for dual eligibles through Medicare both before and after Medicare Part D implementation, which may have eclipsed any effects of the transition. It may also signal that classification of antidepressants as a protected drug class under Medicare Part D was effective in preventing psychiatric medication disruption.